Modulation of insulin secretion by physical training during recovery from protein malnutrition in rats - Moreira, Veridiana Mota; Botezelli, José Diego [UNESP]; Carniero, Everardo Magalhãesc; Latorraca, Márcia Queiroz; Lamp, César Ricardo; de Mello, Maria Alice Rostom [UNESP] (My University, 2009)
Objective: The purpose of the present study was to examine insulin secretion in rats submitted to protein restriction and nutritional recovery associated or not to physical training. Methods: The experiment was designed in two sets of five weeks each. In the first set the rats were fed a nonnal-protein diet(17%-control group) or a low-protein diet (6%-malnourished group) for five weeks. After this, all animals were fed the 17% protein diet and separated into four groups: sedentary control(SC); trained eontrol(TC); sedentary recovered(SR) and trained recovered(TR). TC and TR rats performed swimming exercise. Results: The results indicated efficiency of the 6% protein diet in producing signs of malnutrition, as reduction in body weight gain and serum albumin levels, as well as liver fat. Serum insulin in the fed state and insulin secretion by isolated pancreatic islets in response to glucose were Keduced,but peripheral sensitivity to insulin was increased and glucose tolerance was not changed in the protein deficient rats, indicating adaptation to malnutrition. Diet protocol for nutritional recovery was efficient in repairing body weight gain, serum albumin and liver fat levels of the previously malnourished rats. Glucose induced insulin release by pancreatic islets remained low after nutritional recovery. Insulin secretion by the islets isolated from rats submitted to exercise training during nutritional recovery was improved when compared with the sedentary animals. Conclusion: This indicates that exercise training may be useful in the treatment of protein calorie malnutrition, concerning to glucose induced insulip secretion.
Keywords: Insulin; Nultritional recovery; Physical training; Protein-calorie malnutrition; Rats; albumin; glucose; insulin; albumin blood level; animal experiment; animal model; animal tissue; controlled study; glucose metabolism; glucose tolerance; insulin blood level; insulin release; insulin sensitivity; kinesiotherapy; male; nonhuman; pancreas islet; protein malnutrition; rat; sitting; swimming; therapy effect; weight gain